Children’s and adults’ intuitions about who can own things - Noles, Nicholaus S. (2012)
The understanding that people can own certain things is essential for activities such as trading, lending, sharing, and use of currency. In two studies, children in grades K, 2, and 4 (N = 118) and adults (N = 40) were asked to identify whether four kinds of individuals could be owners: typical humans, non-human animals, artifacts, and atypical humans (e.g., individuals who were sleeping or unable to move). Participants in all age groups attributed ownership to typical humans most often, non-human animals less often, and artifacts least often. In a third study, children and adults (N = 240) attributed property rights to individuals who were awake, asleep, or tied up, but children continued to deny that these rights extend to atypical humans. Although both children and adults use an ontological boundary to guide their ownership attributions, concepts of owners change significantly over the course of development.